Pengaruh Struktur Kepemilikan Manajerial, Leverage, Kompensasi Bonus dan Ukuran Perusahaan Terhadap Manajemen Laba - Oktavia, Rachael; Paramitha, Melvie (Jurnal Syntax Fusion, 2021)
Earnings Management is one of the efforts made by companies to manipulate the numbers in the financial statements so that the company's financial statements can be seen in good condition for investors and other stakeholders. This study aims to determine the effect of managerial ownership structure, leverage, bonus compensation and company size on earnings management in manufacturing companies listed in BEI 2017-2019. The sampling method in this study used purposive sampling so that the researchers found 55 companies that match the criteria in 2017- 2019, so that this study analyzed as many as 165. The testing technique in this research is in the form of classical assumption test, normality test, autocorrelation test, multicollinearity test, heteroscedasticity test, determination coefficient test and T test. The results of the study indicate that Managerial Ownership Structure, Leverage, Bonus Compensation and Company Size do not significantly influence earnings management.